2021
DOI: 10.1002/pits.22571
|View full text |Cite
|
Sign up to set email alerts
|

The linkages between Chinese children's both cognitive engagement and emotional engagement and behavioral engagement: Mediating effect of perceptions of classroom interactions in math

Abstract: Student engagement not only improves student achievement but also affects the dropout rate. Positive classroom interaction between teachers and students enhances student engagement. The interaction between teachers and students is bidirectional, and student engagement can also affect teachers' classroom teaching behavior. Both student engagement and classroom interaction are multidimensional structures, and each dimension is interrelated and mutually influenced. The purpose of this study was to explore the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Emotional engagement refers to student’s positive feeling, attitude, and perception toward learning activities ( Park and Yun, 2017 ; Tvedt et al, 2019 ). Cognitive engagement refers to students’ active involvement in learning with positive psychological status ( Nguyen et al, 2016 ; Yang Y. et al, 2021 ). Among them, behavioral engagement reflects the substantive connotation of student engagement ( Newmann, 1992 ) and it is relatively easier to measure due to their observable characteristics ( Nguyen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional engagement refers to student’s positive feeling, attitude, and perception toward learning activities ( Park and Yun, 2017 ; Tvedt et al, 2019 ). Cognitive engagement refers to students’ active involvement in learning with positive psychological status ( Nguyen et al, 2016 ; Yang Y. et al, 2021 ). Among them, behavioral engagement reflects the substantive connotation of student engagement ( Newmann, 1992 ) and it is relatively easier to measure due to their observable characteristics ( Nguyen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that decreased study well-being experience may trigger negative change in perceived teacher support ( O'Connor, 2010 ; Ouweneel et al, 2011 ; Nurmi and Kiuru, 2015 ; Yang et al, 2021 ; Rautanen et al, 2022 ). Increased study-related burnout symptoms and decreased study engagement were associated with a decline in perceived teacher support, while higher levels of study engagement and low levels of study burnout symptoms were associated with a continuum of positive teacher support experience.…”
Section: Discussionmentioning
confidence: 92%
“…There is increasing research evidence that the interrelationship between teacher support and study well-being may be reciprocal ( Currie, 2014 ; Pitzer and Skinner, 2017 ; Zee et al, 2021 ). It has been found that engaged students are more likely to perceive their teachers as supportive than do their less engaged peers ( O'Connor, 2010 ; Ouweneel et al, 2011 ; Nurmi and Kiuru, 2015 ; Yang et al, 2021 ). In a recent study using a random intercept cross-lagged panel model, we found that study engagement seems to be a stronger, more consistent predictor for later teacher support than the reverse being true ( Rautanen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is algorithmic thinking and problem-solving are advanced cognitive abilities that involve abstract thinking, logical reasoning, problem analysis, and problem-solving skills [9], requiring students to have a certain level of cognitive engagement. In contrast, behavioral engagement often involves surfacelevel behaviors of students, such as completing assignments on time, participating in classroom discussions [43,53], and so on, which may not fully reflect students' algorithmic thinking and problem-solving.…”
Section: Discussionmentioning
confidence: 99%